Implementasi Strategi Marketing Mix Guna Pengembangan Destinasi Wisata di kabupaten Aceh Jaya - Yusnaidi, Yusnaidi; Zhafira, Nabila Hilmy; Damrus, Damrus; Muzakir, Muzakir; Fatmayanti, Fatmayanti (Jurnal Pengabdian Agro and Marine Industry, 2024)
The creation of tourism-aware youth groups, or Pokdarwis, in various communities along the coast of Aceh Jaya Regency has demonstrated actual awareness of the huge potential of tourism. Pokdarwis Pasie Luah, located in Dayah Baroe Village, Krueng Sabee District, is one of these pokdarwis. Teuku Umar University collaborates with Pokdarwis Pasie Luah through community service activities to improve the quality of human resources in the tourism sector and to develop a marketing mix plan to entice tourists to visit tourist spots in Aceh Jaya. The execution of capacity building training and culinary instruction is the concrete aspect of this community service initiative.  Electric scooters, tents, and advertising materials have also been supplied to assist with promotional operations in order to boost visitor visits. Community service activities that contribute to the empowerment of the Pasie Luah Pokdarwis could serve as a model for initiatives to empower other pokdarwis in Aceh Jaya Regency. So that the results of this community program can be sustained and turned into a movement for all tourist stakeholders to work together to promote the Aceh Jaya tourism sector.